NATIONAL BIG DAY COMMEMORATION ACTIVITY: STRENGTHENING THE SENSE OF NATIONALITY OF ELEMENTARY SCHOOL STUDENTS - Rahmah, Sri; Bungai, Joni; Sion, Holten; Indrajaya, Kusnida; Rahman Azahari, Abdul; Edy Setiawan, Wahyu (Acta Scientiae et Intellectus, 2024)
Education in the context of fostering a national spirit in the era of openness is currently a formal institution that is related and has a big responsibility. One of the educational institutions that has a significant effect on the practice of national values is elementary school. The reason is, formal institutions such as elementary schools are the initial foundation for students to pursue higher school levels. The success of character education of a nation can be seen from the national spirit of the students. This national spirit is an embodiment of the character of the nation and can be seen from several indicators, which for elementary school students are celebrating national holidays and participating in national activities. These indicators will later be developed in making statement items on a national attitude scale.